The effect of reducing the thermal contact resistance on the performance of battery thermal management system. (5th February 2021) - Zhang, Wencan; Ling, Guozhi; Zhuang, Liangpiao; Liang, Zhicheng
Summary: With the increasing demand for the driving range of new energy vehicles, the energy of power battery is increasing. As a temperature‐sensitive component, the life, safety, and charge–discharge performance of lithium‐ion power battery will be affected by the working temperature, which makes the battery thermal management system particularly important. Concerning the fact that the thermal contact resistance between the power battery and the heat transfer components has become the bottleneck of battery thermal management system, this study firstly establishes a traditional sandwich structure of phase change material–based thermal management system and then try to reduce the thermal contact resistance of the system by increasing the thermal conductivity of the cooling part and filling the interface with high thermal conductivity material. The thermal contact resistance and the heat flux between the power battery and the thermal management module are experimentally tested and calculated. Based on the external and internal temperature of battery, the effect of contact resistance on the performance of a thermal management system is discussed. The results show that when increasing the thermal conductivity of the cooling part, the battery external and internal temperatures under 3C, 4C, and 5C discharge are reduced by 8.3%, 8.1%, 7.6% and 5.2%, 9.3%, 6.3%, respectively, as compared to the traditional sandwich structure of phase change material–based thermal management system. And the temperatures are further reduced by 6.5%, 7.7%, 6.3% and 7.8%, 6.1%, 7.3% when the interface between the battery and the thermal management module are filled with graphene with high thermal conductivity. Furthermore, the power battery can work within the optimum operating temperature range for a long period and can ensure battery safety by reducing the thermal contact resistance. Abstract : The methods of reducing the thermal contact resistance between the power battery and thermal management module are studied. The heat transfer bottleneck between the battery and the thermal management module is alleviated effectively by increasing the thermal conductivity of the cooling part and filling the interface with graphene solution. The thermal contact resistance at the interface is reduced obviously, and then the performance of BTMS is improved dramatically as compared to the traditional sandwich structure of PCM‐based BTMS.